Effect of m/n = 2/1 neoclassical tearing mode on sawtooth collapse in JT-60U. (21st June 2021) - Bando, T; Wakatsuki, T; Honda, M; Isayama, A; Shinohara, K; Inoue, S; Yoshida, M; Matsunaga, G; Takechi, M; Oyama, N; Ide, S
Abstract: We have investigated the role of the m / n = 2/1 neoclassical tearing mode (NTM) for suppression of the sawtooth collapse in JT-60U from the viewpoint of the anomalous transport of the current diffusion, namely flux pumping. In the stabilization experiments of m / n = 2/1 NTMs by electron cyclotron current drive of JT-60U, it has been clarified that the sawtooth collapses occur during or after the stabilization of m / n = 2/1 NTMs. It is also confirmed that the minimum safety factor, q min, is nearly unity before and after the stabilization of an m / n = 2/1 NTM. While the flux pumping by ELM-NTM coupling was reported in DIII-D, the suppression of the sawtooth collapse is observed without ELMs in this study. On the other hand, it is observed that the sawtooth precursor appears during the stabilization of the m / n = 2/1 NTM accompanying the disappearance of the fluctuation of the n = 1 helical core (HC), which is induced by the m / n = 2/1 NTM. In addition, the modulation of the toroidal rotation velocity having the frequency of the n = 1 HC is observed in the core region. Because the helical flow with HCs is a possible source of the dynamo loop voltage in tokamaks, these observations suggest that the suppression of the sawtooth collapse in JT-60U is realized by the dynamo loop voltage due to the n = 1 HC induced by the m / n = 2/1 NTM. Our result indicates that n = 1 HCs induced by other MHD modes also may induce anomalous current transport in tokamaks.